2005
DOI: 10.1161/01.cir.0000164273.57823.26
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Systolic Performance, Function, and Contractility in Patients With Diastolic Heart Failure

Abstract: Background-Patients with diastolic heart failure (DHF) have significant abnormalities in left ventricular (LV) diastolic function, including slow and delayed relaxation and increased chamber stiffness. Whether and to what extent these abnormalities in diastolic function occur in association with abnormalities in LV systolic performance, function, and contractility has not been investigated thoroughly. Methods and Results-The systolic properties of the LV were examined in 75 patients with heart failure and a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 38 publications
9
195
1
4
Order By: Relevance
“…Analyses were performed to examine the associations of variability of ARD‐z with 4 critical physiological components: (1) cuff diastolic BP, as the steady stress imposed on the Valsalva sinuses at the closure of aortic valve; (2) stroke volume, a measure of left ventricular performance28 that represents the flow volume distending the proximal aorta during ventricular contraction; (3) cuff PP, as the measure of the combined left ventricular ability to expel blood and the aortic capacitance (systolic BP was also used in alternative analyses); and (4) heart rate, as the marker of the frequency of the aortic distension per unit time. In the subpopulation in which applanation tonometry was available, estimates of central systolic diastolic and pulse BP were also evaluated in alternative analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses were performed to examine the associations of variability of ARD‐z with 4 critical physiological components: (1) cuff diastolic BP, as the steady stress imposed on the Valsalva sinuses at the closure of aortic valve; (2) stroke volume, a measure of left ventricular performance28 that represents the flow volume distending the proximal aorta during ventricular contraction; (3) cuff PP, as the measure of the combined left ventricular ability to expel blood and the aortic capacitance (systolic BP was also used in alternative analyses); and (4) heart rate, as the marker of the frequency of the aortic distension per unit time. In the subpopulation in which applanation tonometry was available, estimates of central systolic diastolic and pulse BP were also evaluated in alternative analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional concept of HFNEF is based on sophisticated catheter based conductance studies 15 , 16 demonstrating haemodynamically that HFNEF patients exhibit an upward and leftward shift in end‐diastolic pressure‐volume relationship, whereas the end‐systolic pressure‐volume relationship (end‐systolic elastance) is unaltered or even steeper than in subjects without HF 17 , 18 . Zile, et al 19 demonstrated that HFNEF patients have abnormalities of active LV relaxation (prolonged time constant of relaxation, tau (t), and LV stiffness (increased LV passive stiffness constant (β)) with a resultant increase in left ventricular end‐diastolic pressure (LVEDP) and pulmonary venous pressure even with small changes in LV end‐diastolic volumes, resulting in exertional dyspnoea and even pulmonary oedema 20 .…”
Section: Likely Mechanisms For Diastolic Dysfunctionmentioning
confidence: 99%
“…This relationship may result from the coexistence of systolic and diastolic LV dysfunction exhibited in many patients. 11 The ability of EMAT to detect these changes, even when they occur very rapidly, suggests that this acoustic cardiography parameter can be utilised for monitoring haemodynamic changes that result from therapeutic interventions such as pharmacological therapy, optimisation of cardiac resynchronisation therapy, and ultrafiltration. [12][13][14][15] Our results also suggest that EMAT can be used to detect rapidly occurring impairment of LV function, e.g.…”
Section: Discussionmentioning
confidence: 99%